Security assessment of the selected mobile platform - Iwaniuk, Aleksandra (Journal of Computer Sciences Institute, 2018)
Smartphones were gradually gaining popularity, so as to effectively replace traditional telephones. Devices creates many capabilities, but they can be a source of threats. In this article analyzed Android system security. Author checked what threats lurk for mobile devices and how the Android system tries to protect them. The questionnaire survey checked how the phone screens are blocked and how often changes are made to the blockade. To check if the screen lock can be removed, tests were performed using Google to find the device, as well as Fone. A summary of results was presented and conclusions were drawn.